A comparison of interferometric and single-dish methods to measure distances to pulsar scattering screens. Issue 4 (27th July 2019) - Simard, D; Pen, U-L; Marthi, V R; Brisken, W
Abstract: Investigations of small-scale structure in the interstellar medium through pulsar scintillation and the use of scattering screens as interferometers to resolve pulsar emission regions rely on reconstructions of the spatial distributions of scattered pulsar flux and the distances to scattering screens. In many cases, a single, highly anisotropic scattering screen is responsible for pulsar scintillation. This leads to a sparsity of information in the secondary spectrum which can be leveraged to measure the scattering geometry and map the distribution of scattered images of the pulsar using Very Long Baseline Interferometry. It is also possible to make these same measurements using only the autocorrelations from simultaneous observations at multiple stations. We compare the results from these two methods applied to PSR B0834+06, and find that the two main measurables, the effective distance and velocity, obtained from these two analyses agree to within ∼10 per cent. The relative ease of using autocorrelations from simultaneous single-dish measurements, where the data rates are much lower, only millisecond clock precision is required and the results are less sensitive to the calibration of the data, means that this method opens up a more observationally accessible route for mapping pulsar scattering screens. Since this method does not require the recording and storage of baseband data, it can be applied to ultrawide-band observations, which typically have unmanageable baseband data rates but are vital for testing theoretical models of pulsar scintillation.